1997
DOI: 10.4141/a96-042
|View full text |Cite
|
Sign up to set email alerts
|

Serum mineral concentrations in relation to estrus and conception in beef heifers and cows fed conserved forage

Abstract: Small, J. A., Charmley, E., Rodd, A. V. and Fredeen, A. H. 1997. Serum mineral concentrations in relation to estrus and conception in beef heifers and cows fed conserved forage. Can. J. Anim. Sci. 77: 55-62. A study was undertaken to examine serum mineral concentrations in relation to estrus and first service conception (FSC) in beef cattle fed conserved forage. Blood samples were taken from yearling nulliparous heifers, and suckled 2-yr-old primiparous heifers and multiparous cows at first service which occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Despite B, Cr, Ni, Rb and V potentially being toxic for sheep, these elements can be considered to be beneficial because at low concentrations they may be improve animal performance (Suttle 2010). For instance, an association between poor conception and low serum B concentration has been reported for beef cow herds (Small et al 1997). Similarly, Spears (1984) reported that supplementation of diets that have a Ni concentration range of 0.26-0.85 mg kg −1 with an additional 5 mg Ni as NiCl 2 , increased the ruminal urease, growth rate and feed conversion efficiency of lambs and steers.…”
Section: Potentially Toxic Effectsmentioning
confidence: 96%
“…Despite B, Cr, Ni, Rb and V potentially being toxic for sheep, these elements can be considered to be beneficial because at low concentrations they may be improve animal performance (Suttle 2010). For instance, an association between poor conception and low serum B concentration has been reported for beef cow herds (Small et al 1997). Similarly, Spears (1984) reported that supplementation of diets that have a Ni concentration range of 0.26-0.85 mg kg −1 with an additional 5 mg Ni as NiCl 2 , increased the ruminal urease, growth rate and feed conversion efficiency of lambs and steers.…”
Section: Potentially Toxic Effectsmentioning
confidence: 96%
“…Plasma Cp (and Cu) levels are affected by oestrus, with a particularly evident increase in heifers (Small et al, 1997), and the effect of oestrogen on plasma copper and Cp was well established (Cousins, 1985). It could be hypothesised that an earlier onset of oestrus cycle in H heifers, compared with M heifers, elicited consequences on plasma Cp.…”
Section: Body Measurements and Metabolic Profile Of Growing Heifersmentioning
confidence: 97%
“…Similar concentrations of boron (µg/mL) were reported in the plasma of humans (0.017-0.191) (Ferrando et al 1993;Hunt et al 1997;Iyengar et al 1990;Mauras et al 1986;Usuda et al 1997;Wallace et al 2002;Ward 1993), rats (0.038-0.039) (Seaborn and Nielsen 1994;Vaziri et al 2001), chicks (0.047-0.152) (Hunt 1989;Hunt 1996), cows (0.052-0.153) (Hunt 1996;Small et al 1997), lambs (0.163) (Hunt 1996), pigs (0.126) (Hunt 1996), and horses (0.227) (Hunt 1996). Liver boron concentrations (µg/g; dry weight) are similar in humans (1.1-5.4) (Shuler et al 1990;Ward 1987), rats (0.51) , chicks (1.01-4.4) (Rossi et al 1993), and cows (3.3) (Ward 1987); for brain tissue (µg/g; dry weight), similar in humans (0.87) (Shuler et al 1990), rats (0.64) , and chicks (1.01-1.05); for bone tissue (µg/g; dry weight), similar in humans (1.6) (Ward 1993), rats (1.3) , chicks (0.59-0.64) Hunt et al 1994;Wilson and Ruszler 1996), and mule deer (1.7) (Stelter 1980).…”
Section: Boron Concentrations In Healthy Tissuesmentioning
confidence: 51%